Spillover effects on infant caregiving and domestic work during the poriborton clean cookstove trial - Md. Khobair Hossain; Neeloy Ashraful Alam; Elizabeth K. Kirkwood; Sajia Islam; Sk Masum Billah; Md. Rashidul Azad; S. M. Rokonuzzaman; Camille Raynes-Greenow (PLoS ONE, 2026)
Quality care during early childhood is essential for life-long health, well-being, and productivity. Recognizing the global importance of advancing early childhood development strategies, this study conducted in-depth, face-to-face interviews with women, their husbands, and mothers-in-law to explore perceived shifts in childcare roles among participants of Poriborton Trial, a randomized controlled trial of Liquefied Petroleum Gas (LPG) cookstoves. These interviews aimed to capture diverse perspectives on evolving caregiving dynamics and explored mothers’ perspectives. Qualitative data were systematically analyzed using thematic analysis following an iterative process of coding and theme development. We found that LPG stoves facilitated notable changes in caregiving. Firstly, LPG adoption reduced cooking time and decreased workload, which increased women’s time availability for childcare. Secondly, mothers reported a greater capacity to balance household tasks and childcare, fostering more frequent interaction with their children. Thirdly, the study identified enhanced childcare practices, with LPG use enabling women to be more responsive to their children's needs particularly during illness and to maintain closer physical proximity. The adoption of LPG stoves has multiple positive impacts on the childcare roles of breastfeeding women, empowering them to engage more fully in their children’s upbringing. Building on these qualitative insights into how LPG use may enhance childcare, future quantitative research is recommended to rigorously assess outcomes such as reductions in maternal stress, increased time availability for mothers, and changes in mother-child attachment attributable to LPG stove adoption.